The Main Issues of the Natural Law Theory of Human Rights - Kochubaev, A. (Bulletin of Yerevan University C: Jurisprudence, 2020)
This scientific article is devoted to the one of the most important issues of the general theory of law - the natural law thеory of human rights. The main issues and the importance of the natural law doctrine, as well as the advantages and disadvantages of the theory under discussion from the point of view of modern globalization are discussed in the article presented.
Keywords: natural law theory, human rights, natural law, positive law